ANALISIS KEBERADAAN PEWARNA SINTETIS (RHODAMIN B) PADA LIPSTIK YANG DIJUAL DI PASAR DESA TANJUNG BATU KABUPATEN OGAN ILIR - Indah Hamida (JURNAL SMART ANKES, 2022)
Rhodamine B is a coloring agent whose use is prohibited in cosmetic products because it is used in coloring paper and textiles. The purpose of this study was to find out the description of the existence of the synthetic dye Rhodamine B in lipsticks sold at the Tanjung Batu village market, Ogan ilir district, in 2022 based on color, price and brand. The design used in this research is descriptive and the method used is purposive sampling. The inspection method used is the chromatographic method. The results of the research that was conducted on 10 samples found 1 sample (10%) positive and 9 samples (90%) negative. Based on the color of the lipstick, there were 2 samples (100%) which were bright red negative for Rhodamin B, 6 samples (100%) who were pink negative for Rhodamin B, and 4 samples of lipstick with brick red color, 1 sample of lipstick (25%) was positive for Rhodamin B and 3 samples (75%) were negative for Rhodamine B. Based on price ≥ Rp. 20,000, 5 samples (100%) were negative (-) containing Rhodamin B, while < Rp. 20,000, 1 sample (20%) was positive (+) containing Rhodamin B. Based on the brands of 10 lipstick samples sold in Tanjung Batu Village, District Ogan Ilir 2022 was studied and got 1 sample (20%) positive results with a brand that has a BPOM permit.